2007
DOI: 10.1080/10256010701362112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radioactive and non-radioactive mercury on wheat germination and the anti-toxic role of glutathione

Abstract: Studies to test the noxious effect of mercury ions on wheat germination and seedling growth showed that germination rate, shoot length, and fresh weights varied as a function of their concentration in the treatment solutions. At the same concentration, the radioactive mercury proved to be more harmful to the living seeds and seedlings. The detoxification action of glutathione for both radioactive and non-radioactive mercury was also followed. After a seven-day period of germination in the presence of the inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…26 However, cysteine-containing peptides, such as glutathione, have the highest affinity toward heavy metal ions, whereas glycine-rich P19 peptides have a lower one. [37][38][39] our results are concordant with the mechanism previously described, whereby an analog of the human albumin N-terminus (Asp-Ala-His-Lys) prevents formation of copper-induced reactive oxygen species and potentially provide therapeutic benefit for roS-related diseases. 28 A neuroprotective ability was described in the case of tetrapeptide L-Asp-Ala-His-Lys in permanent middle cerebral artery occlusion in rats.…”
Section: Biomedical Implicationssupporting
confidence: 90%
“…26 However, cysteine-containing peptides, such as glutathione, have the highest affinity toward heavy metal ions, whereas glycine-rich P19 peptides have a lower one. [37][38][39] our results are concordant with the mechanism previously described, whereby an analog of the human albumin N-terminus (Asp-Ala-His-Lys) prevents formation of copper-induced reactive oxygen species and potentially provide therapeutic benefit for roS-related diseases. 28 A neuroprotective ability was described in the case of tetrapeptide L-Asp-Ala-His-Lys in permanent middle cerebral artery occlusion in rats.…”
Section: Biomedical Implicationssupporting
confidence: 90%
“…The previous results demonstrated that potential target sites for the evaluation of metal binding need to be carefully analyzed for interfering metal-metal interactions [19,[23][24][25][26][27][28]. In this study, decreases of bound silver by Aβ, and an increase in bound copper were the most pronounced interactions between the two toxic metals (Figure 3).…”
Section: Metal-metal Interactions During the Binding Processmentioning
confidence: 83%
“…Mass spectrometric analysis of DNP degradation products revealed the presence of 6-hydroxy-3,5-dinitrohexa-2,4-dienal as the main constituent of the irradiated solution. Moreover, both the infrared spectroscopy and the wheat germination experiment , [14][15][16][17] using the supernatant that contained photodegraded DNP, confirmed the fast disappearance of the toxicity. Besides, Fourier transform-infrared (FT-IR) spectra indicated the formation of a nonaromatic aldehyde.…”
Section: Introductionmentioning
confidence: 90%